Ahlaki İkilem Tekniğine Dayalı Çalışma Yaprağına İlişkin 7. Sınıf Öğrencilerinin Görüşleri: Farklılıklara Saygı Değeri - Yalman, Emine; Aktepe, Vedat; Uzunöz, Abdülkadir (Muş Alparslan Üniversitesi, 2018)
It is aimed to determine the student responsesto questions about The Value of Respect for Diversity in a worksheet that isbased on the moral dilemma technique. The research is a qualitative study andcase study method is used, and it has been carried out with a holistic singlecase design. The research group consists of twenty seven students studying inthe seventh grade of a public school in central Nevşehir. As data collectiontool, worksheets based on the value of Respect for Diversity prepared by theresearchers were used. Content analysis was performed on the data obtained. Inorder to increase the internal reliability and validity of the findings of thestudy, the students'opinions were given by making direct citations. The mosteffective factor in their moral reasoning process was positive communicationwhile other important factors were empathy and respect.

Buaraştırmada ahlaki ikilem tekniğine dayalı hazırlanan farklılıklara saygıdeğeri çalışma yaprağındaki sorulara verilen öğrenci cevaplarının tespitedilmesi amaçlanmıştır. Nitel bir çalışma olan bu araştırmada örnek olayyöntemi kullanılmıştır. Araştırma bütüncül tek durum deseni ile yürütülmüştür.Araştırma grubunu Nevşehir merkezindeki bir devlet okulunun yedinci sınıfındaöğrenim gören yirmi yedi öğrenci oluşturmaktadır. Veri toplama aracı olarakaraştırmacılar tarafından hazırlanan farklılıklara saygı çalışma yaprağıkullanılmıştır. Elde edilen verilere içerik analizi yapılmıştır. Araştırmabulgularının iç tutarlığı ve geçerliğini artırmak amacıyla, her bir temanınaltında öğrenci görüşlerini yansıtan doğrudan alıntılara yer verilmiştir.Öğrencilerin ahlaki muhakeme sürecinde en etkili faktör olumlu iletişim kurmakolurken, etkisi olan diğer önemli faktörler de empati kurmak ve saygılı olmakolarak belirlenmiştir.
Views of Seventh Grade Students about Work Sheets based on the Moral Dilemma Technique: the value of Respect for Diversity
anemon
Keywords: Social Studies; Value; Value Teaching; Moral Dilemma; Respect; Sosyal Bilgiler; Değer; Ahlaki İkilem; Saygı; Değer Öğretim